The Effect of Melatonin on Platelet Levels in Wistar Rat After Burns in Two Days - Qusairi, Velya Lizhariany Hafidha; Purwoko, Purwoko; Purnomo, Heri Dwi (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2024)
Background : Burns can caused by high temperatures. Burns have an impact on platelet levels and hemostatic regulation. Melatonin is a therapeutic agent that can increase platelet levels on burns by neutralizing Reactive Oxygen Species (ROS) and Reactive Nitrogen Species (RNS) so it can suppress tissue damage due to burns. This study aims to determine the effect of giving melatonin on the platelet levels of burnt wistar rats in two daysMethods : This is experimental study with a sample of 12 Wistar rats that matched the inclusion and exclusion criteria. Rats were divided into two groups, namely K1 as control and K2 as a group that was given melatonin at a dose of 10 mg/kg. Platelet levels were measured at T1 (0th hour post burn), T2 (24th hour post burn), and T3 (48th hour post burn). The data were analyzed by the Shapiro-Wilk normality test, followed by Parametric Paired t-Test and the Independent t-Test.Result : This experimental results there was a significant increase in the number of platelets between T2 and T3 and between T1 and T3 in control group. And in K2, there was a significant decrease in the number of platelets between T1 and T2 and between T2 and T3. Meanwhile, between T1 and T3 there was a significant increase in platelet levels.Conclusion: Melatonin can significantly increase the platelet levels of burn Wistar rats at 48 hours post-burn.